BaLu6(Si2O7)2(Si3O10):Ce3+, Tb3+: A novel blue-green emission phosphor via energy transfer for UV LEDs. (April 2017) - Li, Kai; Lian, Hongzhou; Han, Yanqiu; Shang, Mengmeng; Van Deun, Rik; Lin, Jun
Abstract: A series of novel blue-green emission phosphors BaLu6 (Si2 O7 )2 (Si3 O10 ):Ce 3+, Tb 3+ (BLSO:Ce 3+, Tb 3+ ) were synthesized via the high-temperature solid-state reaction route. Many characterizations such as X-ray diffraction (XRD), scanning electron microscopy (SEM), transmission electron microscopy (TEM), Fourier transform infrared spectroscopy (FT-IR) were conducted to analyze the phase and structure of as-prepared samples. Photoluminescence (PL) properties illustrated that Ce 3+ singly doped BLSO can produce a broad band ranging from 365 to 550 nm upon UV excitation, which overlapped the excitation spectrum of Tb 3+ monitored at 550 nm emission. Energy transfer phenomenon from Ce 3+ to Tb 3+ in this kind of phosphor was demonstrated from the variations of emission spectra and the decrease of Ce 3+ fluorescent decay lifetime in Ce 3+ -Tb 3+ co-doped BLSO, based on which the emission color can be tuned from bright blue to green upon UV excitation. The energy transfer mechanism from Ce 3+ to Tb 3+ was determined to be electric dipole-quadrupole interaction. Moreover, the temperature-dependent PL of representative BLSO:0.18Ce 3+, 1.00Tb 3+ was supplied in this manuscript, which indicated the good thermal stability of this kind of phosphor. The results show that BLSO:Ce 3+, Tb 3+ phosphors can be as a potential candidate of blue-green component in phosphor-converted UV LEDs. Graphical abstract: A series of novel blue-green emission phosphors BaLu6 (Si2 O7 )2 (Si3 O10 ):Ce 3+, Tb 3+ (BLSO:Ce 3+, Tb 3+ ) have been synthesized and investigated. Highlights: BaLu6 (Si2 O7 )2 (Si3 O10 ):Ce 3+, Tb 3+ phosphors were synthesized for the first time. Tunable color from blue to green was realized via energy transfer from Ce 3+ to Tb 3+ . The BaLu6 (Si2 O7 )2 (Si3 O10 ):Ce 3+, Tb 3+ phosphors exhibited good thermal stability. BaLu6 (Si2 O7 )2 (Si3 O10 ):Ce 3+, Tb 3+ is a promising blue-green phosphor for LED.